1994
DOI: 10.1159/000227355
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Detection of P-Glycoprotein: Initial Expression Correlates with Survival in Renal Cell Carcinoma Patients

Abstract: We evaluated 28 patients with advanced renal cell carcinoma for the initial expression of P-glycoprotein (MDR1 gene product) employing immunocytochemistry. Tumor specimens were obtained upon primary tumor nephrectomy. In all patients, progression-free survival time following nephrectomy was evaluated and correlated statistically with the staining results. Progression-free survival of patients with no or very few ( < 1%) P-glycoprotein-positive tumor cells (n = 8, median survival 27.0 months) was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 10 publications
(12 reference statements)
2
9
0
3
Order By: Relevance
“…Our results support the observation of Duensing et al[36] of a longer progression-free survival in patients with no or very few MDR-1 positive tumour cells compared to the group of patients with several positive tumour cells, but are in disagreement with the report of Oudard et al[37]. …”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our results support the observation of Duensing et al[36] of a longer progression-free survival in patients with no or very few MDR-1 positive tumour cells compared to the group of patients with several positive tumour cells, but are in disagreement with the report of Oudard et al[37]. …”
Section: Discussionsupporting
confidence: 50%
“…In renal cell carcinoma, Duensing had already found a longer progression-free survival in patients with no or very few MDR-1 positive tumour cells compared to the group of patients with higher MDR-1 positivity [36]. However, this association was not confirmed by Oudard, who showed a tendency for a lower MDR-1 expression in advanced RCCs.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several studies have shown a decreased expression of PgP transcripts or protein in association with higher-grade tumors 8,9,13,37,38 and metastatic sites, 38 although not found in all studies, 6,39 and generally weaker staining in renal tumors compared with normal tubular staining, 8,13,35,40 possibly supporting a loss of expression with increasing dedifferentiation. Interestingly, 2 separate studies have reported a potential prognostic use of PgP expression, 39,41 although with conflicting results. The findings of these and our studies with relatively few tumors showing upregulated PgP expression are unexpected, given the hypoxia-inducible factor-1 (HIF-1)-dependent upregulation of the PgP/MDR-1 gene, 42 particularly with both the known hypoxic environment of renal tumors and the loss of VHL function and consequent upregulation of HIF-1␣ in the majority of clear cell renal cancers.…”
Section: Discussionmentioning
confidence: 78%
“…Schneider et al 31) speculated that the genes associated with oncogenic development may also activate P-gp concomitantly in human cancers. Duensing et al 43) showed that P-gp is a marker Furthermore, previous reports demonstrated that MDR1 and MRP play important roles in resistance to Topo II inhibitors such as etoposide or adriamycin. 8,22,23) We did not detect any differences between the steady-state levels of MDR1 or MRP mRNA in HNSCC and HNM, suggesting that it may be worth considering the use of topoisomerase-targeting antitumor drugs against HNSCC.…”
Section: Discussionmentioning
confidence: 99%